Development of a heterologous enzyme-linked immunosorbent assay for organophosphorus pesticides with phage-borne peptide - Hua, Xiude (RSC Adv, 2014)
An enzyme-linked immunosorbent assay (ELISA) was developed to detect organophosphorus pesticides using a phage-borne peptide that was isolated from a cyclic 8-residue peptide phage library. The IC(50) values of the phage ELISA ranged from 1.4 to 92.1 μg L(−1) for eight organophosphorus pesticides (parathion-methyl, parathion, fenitrothion, cyanophos, EPN, paraoxon-methyl, paraoxon, fenitrooxon). The sensitivity was improved 120- and 2-fold compared to conventional homologous and heterologous ELISA, respectively. The selectivity of the phage ELISA was evaluated by measuring its cross-reactivity with 23 organophosphorus pesticides, among which eight were the main cross-reactants. The spike recoveries were between 66.1% and 101.6% for the detection of single pesticide residues of parathion-methyl, parathion and fenitrothion in Chinese cabbage, apple and greengrocery, and all of the coefficient of variation were less than or equal to 15.9%. Moreover, the phage ELISA results were validated by gas chromatography. The results indicate that isolating phage-borne peptides from phage display libraries is an alternative method for the development of a heterologous immunoassay and that the developed assay has a lower limit of detection than the chemically synthesized competitor assay.